LITERARY ADAPTATION’S EFFECTS ON PLOT AND CHARACTER IN DR. ZHIVAGO: AN INTERTEXTUAL STUDY - Rahmawati, Movi Riana (ENGLISH JOURNAL, 2016)
This research try to reveal what are the elements of plot and characters that are retained, exaggerated and glossed over along with literary adaptation process. This research is an inter textual studies with Qualitative Descriptive analysis. Dr. Zhivago is a story with Russian revolution background about the struggle of a doctor in finding his lost love, identity, and the essence of life. This study will specifically compare the novel and film in terms of plot and character. The writer wants to reveal which elements that retained and whether there is any distortion or exaggeration in plot and character as a result of the process of literary adaptation. The writer will analyze the novel and the film as source of data. Through the analysis, it can be concluded that most of the elements are retained, but there are a number of distortions and exaggerations in the plot and character as a result of the process of literary adaptation from novel to film. Obvious distortions described in the plot is the elimination of political background plots at that time. This is because, at that moment, most of political films were strongly opposed and banned. Intertextuality emphasizes the distortion compensated in the film through some other elements such as pictures, music, and others. Similar things happen to the characters where some of the characters are exaggerated when they are potrayed in the film. For example General Yevgarf Zhivago is potrayed as a true hero in the film, but as a minor character in the novel. The distortion is the compensation of the elimination of several political characters. The purpose of the distortions of some characters in the film, which are the minority during the revolution, is to avoid political incorrectness. The distortions and exaggerations of the plot and character turn to affect the overall plot and theme of the story. When the novel is adapted into a film, Dr Zhivago turns to be a romance with the background of the Russian revolution, whereas in the novel, the main concern of the author is on the impact of the revolution to oppressed minority.